(untitled) (Journal of Hama University, 2022)
The research aims to study the pathological anatomical changes after the administration of dexamethasone on the lymphoid tissue (thymus _ fabricia follicle ) and liver in meat chickens . Used in this study (100) birds divided into five groups, each of which includes (20) birds, where the first group represents the group witness and the birds were injected into the chest muscle dexamethasone in the other three groups starting from the age of ten days and for three consecutive days and fixed doses for each group reached ( 0.5-1-2.5 the fifth groups were given dexamethasone by drinking water starting from the tenth day on a daily basis at a dose of 1 mg / L for 20 days from the start of the experiment, and then collected tissue samples from the lymphatic and hepatic organs , The samples were stabilized with a 10% neutral formalin solution, the samples were prepared with paraffin Fusion and tissue strips were made with hematoxylin and eosin . No pathological anatomical changes were observed in the fabricia pod , thymus and liver in general, except for the presence of hyperemia in one thymus lobe in the third group given the dose of 1 mg /kg after (72) hours of injection as well as peripheral hyperemia in the liver 24 hours after the first injection in the intramuscular injection groups and continued until the end of the experiment .And congestion in the fifth time in the drinking water group. The histological sections of the fabricia follicle showed an increase in programmed cell death in lymphocytes in addition to hemorrhage and congestion between lymphoid follicles in thymus in the third and fourth group given (1 -2.5 ) mg respectively and more clearly after (72 ) hours of injection, also observed in thymus there is an increase in programmed cell death in cells after ( 72 ) hours, observed in reduced reactivity in the drinking water group was observed on the twentieth day From experience.